2012
DOI: 10.3354/meps09650
|View full text |Cite
|
Sign up to set email alerts
|

Assembly rules for aggregate-species production models: simulations in support of management strategy evaluation

Abstract: Ecosystem-based fisheries management (EBFM) emphasizes sustainability at multiple levels of organization beyond single target species. Therefore, biological reference points (BRPs) for aggregated groups are required, which optimize yields while preventing overexploitation of individual species. We evaluate the tradeoffs between yield and biodiversity objectives for a wide range of aggregation strategies using multispecies surplus production models and comparing 2 simulated fish communities. We simulated popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 53 publications
(60 reference statements)
2
52
0
Order By: Relevance
“…Aggregate groups also tend to be more stable than the indi vidual components (Fogarty & Murawski 1998, Auster & Link 2009, so this method can be used initially to determine robust harvest levels to achieve system and aggregate group level BRPs. More complex models which explicitly include multiple species can then be used to examine the implications of those harvest strategies on the individual components of an aggregated group (as was done by Gaichas et al 2012). This 2-stage approach is also recommended due to the observation that aggregated models may have very different characteristics regarding community stability, resilience, and other behaviors of the components modeled, than one in which the components are disaggregated (Pinnegar et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggregate groups also tend to be more stable than the indi vidual components (Fogarty & Murawski 1998, Auster & Link 2009, so this method can be used initially to determine robust harvest levels to achieve system and aggregate group level BRPs. More complex models which explicitly include multiple species can then be used to examine the implications of those harvest strategies on the individual components of an aggregated group (as was done by Gaichas et al 2012). This 2-stage approach is also recommended due to the observation that aggregated models may have very different characteristics regarding community stability, resilience, and other behaviors of the components modeled, than one in which the components are disaggregated (Pinnegar et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The drawbacks are those usually associated with production models (e.g. missing internal stage or age related dynamics, and ignoring different life history characteristics of individual species within an aggregation, which is explored more thoroughly in Gaichas et al 2012, this Theme Section).…”
Section: Introductionmentioning
confidence: 99%
“…Several instances where such simulation testing has occurred demonstrate improvements across a range of not only yield, but other fisheries objectives (Worm et al 2009;Link et al 2010;Fulton et al 2011;Kaplan and Leonard 2012;Fay et al 2013Fay et al , 2015Smith et al 2015;Jacobsen et al 2017). Additional contrasts have similarly elucidated the performance of OY estimates empirically, with a range of studies having similarly explored this issue (e.g., Ralston and Polovina 1982;Mueter and Megrey 2006;Fogarty et al 2008Fogarty et al , 2012Worm et al 2009;Sparholt and Cook 2010;Gaichas et al 2012;Lucey et al 2012;Rosenberg et al 2014). A few common outcomes emerge from this collective body of work.…”
Section: Addressing Pragmatic Considerations Of System-level Thinkingmentioning
confidence: 99%
“…Several theoretical, simulation, and contextual considerations have explored this approach Link 2009, 2012;Worm et al 2009;Bundy et al 2012;Fay et al 2013Fay et al , 2015Fogarty 2014;Gaichas et al 2017;Rosenberg et al 2014;Rindorf et al 2017a) and found the method performs as one would expect from hierarchy theory, namely that resulting model outputs are consistent with the portfolio effect Jin et al 2016). Many works (e.g., Mueter and Megrey 2006;Fogarty et al 2008Fogarty et al , 2012Christensen et al 2009;Gaichas et al 2012;Lucey et al 2012;Rosenberg et al 2014;Rindorf et al 2017aRindorf et al , 2017b have examined these approaches, tested the analytical methods, explored the robustness and vagaries of the results, and generally arrived at the conclusion that at the very least, the analytical methodologies and considerations are not a limitation for the adoption of this systems approach. More so, the results are generally repeatable, robust, and ecologically defensible.…”
Section: Addressing Pragmatic Considerations Of System-level Thinkingmentioning
confidence: 99%
See 1 more Smart Citation